American capitalism: the concept of countervailing power - "Galbraith, John Kenneth" (New York, 1956)
In his new introduction to this classic text on political economy, Galbraith reasserts the validity of the core thesis of American Capitalism: The best and established answer to economic power is the building of countervailing power. The trade union remains an equalizing force in the labor markets, and the chain store is the best answer to the market power of big food companies. This work remains an essential guidepost of American mores as well as that as of the American economy.
Keywords: Economics